In‐situ investigation of concentration of strains around an implanted bar - Keras, Valerijus; Roličius, Jonas (Journal of Civil Engineering and Management, 2005)
For constructional purposes reinforcement bars or connecting elements (implants) of a stronger material are installed in concrete, plastic, timber or another similar material‐matrix. Structural concepts are being developed where implants are used both as reinforcing and connecting elements. The implants increase the strength and rigidity of structures. However, investigation of functioning of implants and generalisation of data obtained up to now have been premature. Moreover, they do not help us to understand some empiric facts. In the course of the above‐mentioned tests (data concerning the tests were presented in previously published works), steel bars‐implants with one meter thread were screwed and glued into timber and then attempts to extract them were made. During the test, the bars were screwed into holes in the timber filled with glue. The angle at which the implant was screwed through the layers of wood, the type of glue and some other factors were changed. Such characteristics as strength, strain, breakage and the process of deformation were analysed. Deformainijų koncentracijos implantuoto strypo aplinkoje ir jų natūriniai tyrimai Santrauka. Betonuose, plastike, medienoje ar panašioje medžiagoje – matricoje konstrukciniais sumetimais dažnai yra įterpiami stipresnės medžiagos strypai – armuojantys implantai. Tobulinami inžineriniai kompleksinio implantų naudojimo sprendimai, kai jie naudojami ir kaip armavimo, ir kaip jungimo priemonės. Tačiau iki šiol sukaupti implantų darbo tyrimu duomenys nėra išsamūs, jų apibendrinimai – kiek skuboti. Tęsiant šiuos tyrimus, buvo bandomi įsriegti ir įklijuoti ar tik įklijuoti į pušinę medieną stambieji metrinio sriegio strypai‐implantai. Buvo keičiamas implanto su medienos sluoksniais sudaromas kampas, klijų pobūdis, kiti veiksniai. Buvo aprašytos stiprumo, deformatyvumo, irimo charakteristikos, nagrinėtų procesu pobūdis. Pasiūlytos empirinės pareinamybės: vidutinė, gauta, remiantis bandymų duomenimis, techniškai patikima šių duomenų aibėje ir pan. Raktiniai žodžiai: mediena, implantai, klijai, stiprumas, deformatyvumas, irimas. First Published Online: 14 Oct 2010